Embolus entrapped in patent foramen ovale: impending paradoxical embolism - Podroužková, Helena; Horváth, Vladimír; Hlinomaz, Ota; Bedan, Jan; Bambuch, Miroslav; Němec, Petr; Orban, Marek (The Annals of thoracic surgery, 2014)
An impending paradoxical embolism is a rare finding, with fewer than 200 cases being documented so far. A 68-year-old woman, who presented with 3 weeks of increasing exertional dyspnea and exercise intolerance, underwent transesophageal echocardiography with a finding of an embolus in both right and left atria. At an emergent cardiac surgery, a worm-shaped, 5-cm-long thrombus was found in the right atrium, it was protruding to left atrium through the foramen ovale. The thrombus was removed intact, and the foramen ovale was closed. By our experience, an emergent cardiac surgery should always be considered as a treatment option for impending paradoxical embolism.
Keywords: Cardiac Surgical Procedures; počítačová rentgenová tomografie; echokardiografie transezofageální; echokardiografie trojrozměrná; foramen ovale apertum; trombektomie; Diagnosis, Differential; Aged; senioři; Echocardiography, Transesophageal; Embolism, Paradoxical; paradoxní embolie; Tomography, X-Ray Computed; Foramen Ovale, Patent; lidé; ženské pohlaví; Humans; diferenciální diagnóza; Echocardiography, Three-Dimensional; Female; kardiochirurgické výkony; Thrombectomy